Effect of Die Retention Time on Pellet Quality and Phytase Stability of a Corn-Soybean Meal Swine Diet - M. Saensukjaroenphon; C. E. Evans; C. K. Jones; C. H. Fahrenholz; C. B Paulk; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2019)
Phytase is a phosphohydrolytic enzyme that releases phosphorus from phytate in animal feed. However, pelleting is a thermal process that can denature phytase. It is hypothesized that there are many factors that can account for phytase denaturing during the pelleting process, such as pellet mill model, die length to diameter ratio (L:D), steam quality, and residence time in conditioner and die. Therefore, the objective of this experiment was to determine the effect of pellet mill model, die thickness, and die retention time on pellet quality and phytase stability. Treatments were arranged as a completely randomized design to determine the effect of die retention time (RT). Diets were pelleted using either a 1012-2 HD California Pellet Mill (CPM) Master Model or a 3016-4 HD CPM Master Model equipped with a 3/16 × 2 in (10.6 L:D), a 3/16 × 1 1/4 in (6.6 L:D) or a 3/16 × 1 3/4 in (9.3 L:D) with 30 sec conditioning retention time at 185°F with designated production rate. These processing conditions were used to create the following RT treatments: 10.6 L:D with 4.3 sec RT, 10.6 L:D with 2.9 sec RT, 9.3 L:D with 1.7 sec RT, 9.3 L:D with 1.1 sec RT, 6.6 L:D with 2.6 sec RT, and 6.6 L:D with 1.6 sec RT. The pellet mills were run 3 separate times to provide 3 replicates for each treatment. There was an overall effect (P<0.001) of treatment on phytase stability in cooled pellets. When using the 1012 PM, phytase was more stable regardless of die retention time when diets were manufactured using the 6.6 L:D die compared to the 10.6 L:D die (P<0.05). The hot pellet temperature of 10.6 L:D die was 195–211°F, while 6.6 L:D die was 184–189°F. However, the phytase stability was similar between the feed pelleted with 1012 PM equipped with 6.6 L:D die and the 3016 PM equipped with 9.3 L:D regardless of retention time (P>0.05). The hot pellet temperature of feed pelleted with the 1012 PM equipped with 6.6 L:D die was 184–189°F, while the feed pelleted with the 3016 die equipped with 9.3 L:D die was 180–183°F. There was also a quadratic decrease in phytase stability as the die L:D increased (P<0.0001). There- fore, the pellet mill size or die retention time did not affect phytase stability when the hot pellet temperature was less than 189°F. Pellet quality increased (linear;P<0.0001 for standard pellet durability index (PDI) or quadratic;P<0.0001 for modified PDI) as die L:D increased. The die L:D had greater effects on both PDI methods than the die retention time. However, increased die retention time improved (P<0.05) pellet quality when the feed was pelleted with 6.6 L:D, but not when pelleted using the 9.3 or 10.6 L:D. In conclusion, the phytase that was produced byTrichoderma reeseistrain could tolerate hot pellet temperatures up to 189°F, regardless of pellet mill model, die thickness, and die retention time. However, phytase stability was dramatically reduced when hot pellet temperatures ranged from 195–211°F. Therefore, hot pellet temperatures should be measured to monitor phytase stability. Increasing the die L:D had the greatest effect on improving pellet quality.
Keywords: retention time; phytase stability; pelleting